Internal Supply Chain Risk Management Using Failure Mode and Effect Analysis (FMEA) and Value at Risk (VaR) (Case Study in PT Agro Muda Berkarya) - Abdul Malik Sulaiman Said; Naning Aranti Wessiani (Jurnal Teknik ITS, 2021)
In the agricultural industry, the risk variability in the internal supply chain is very high which is influenced by various factors, namely humans, weather, nutrition, pests, and others. These risks must be mapped so that companies in the agricultural industry can avoid failed harvest, increase their productivity, and has the capability in producing quality crops. The high possibility of risk in the agricultural industry, especially in Indonesia, reducing the possibility of investment by private or foreign companies, this can be corrected by having a clear risk assessment in any agricultural commodity investment plans. The investment plan assessment is carried out in order to determine the probability of possible losses and profits. PT. Agro Muda Berkarya is a company engaged in the agricultural sector, producing and trading agricultural commodities on a national and international scale. This company, which is located in Bogor, generates its operational activities with an initial focus on food crop cultivation, PT. Agro Muda Berkarya started production with an initial capital of 5000m2 and produced ginger as main crop with luffa as the intercopping crop. In carrying out the planting process, PT Agro Muda Berkarya wants to know the risks that can arise and mitigation action throughout the internal supply chain and probability of return in the business investment. This business investment focuses on luffa and ginger plants. In this final project, identification and risk profiling was carried out using Failure Mode & Effect Analysis (FMEA) and Value at Risk (VaR) with the Monte Carlo Simulation methodology to determine the probability of losses and profits on investing in ginger and oyong as intercopping plant. Last, Return on Investment (ROI) were calculated in order to understand company business performace.